Effects of sugar type on the physicochemical and sensorial properties of miracle fruit (Crescentia cujete) wine. - Andigan, Revie Jean D. (2023.)
This study aimed to assess and evaluate the physicochemical and sensorial properties of calabash wines fermented using different types of sugar. Coco sugar, muscovado sugar, and brown sugar were incorporated as fermentation substrates for wine yeast. The total soluble solids (TSS), titratable acidity (TA), pH, alcohol content, and total phenolic content (TPC) were measured every 4 days throughout the 16-day fermentation. Sensory evaluation was used to determine the most preferred calabash wine formulation as well as to assess its sensorial properties in terms of color, taste, and aroma. Results revealed that the alcohol content with different sugar types were within the standard limits for wine, with actual values recorded at 15.02%, 14.08%, and 13.37% for brown sugar, coco sugar, and muscovado sugar, respectively. As fermentation occurred, alcohol content increased while TSS levels decreased due to the presence of nutrients in the different sugar types. TPC for all wines showed high amounts of phenolic compounds due to the high TPC present in calabash fruit. The wines were subjected to a preference ranking test and the formulation with muscovado sugar was found to be the most preferred. Based on the descriptive test, it was revealed that MS calabash wine is taupe in color, has a moderate sweetness with an average score of 6.87, and has a strong alcoholic aroma with an average score of 12.47 using 15-cm line scale. The 9-point hedonic rating revealed that the product was considered as like moderately.
Thesis (Undergraduate, Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Wine -- Miracle fruit